Happiness Model and Educator Performance in The Teaching and Learning Process - Kartilah, Tetet; Cahyati, Peni; Kanya, Nita (Green Publisher, 2023)
The performance of Vocational Program lecturers at Private Polytechnics in West Java shows signs of being below par. This study aims to investigate the impact of organizational culture, lecturer morale, and empowerment on lecturer happiness, and how these factors ultimately affect the performance of lecturers at private polytechnic universities in West Java. The primary framework utilized in this research is a combination of Management Science and Organizational Theory. By employing a Middle Range Theory approach, the study also incorporates elements of Human Resource Management and Organizational Behavior. Additionally, the study draws upon the applied theories of Organizational Culture, Morale, Empowerment, Happiness, and Performance. A comprehensive review of the literature has led to the formulation of the following hypotheses: Organizational culture and work enthusiasm have a simultaneous influence on happiness, organizational culture directly impacts happiness, work enthusiasm significantly affects happiness, and happiness directly influences lecturer performance.